How Thai Women Manage Living in the Context of Intimate Partner Violence - Thananowan, Nanthana (Journal of interpersonal violence, 2021)
Although there is literature that describes coping strategies of women who experience intimate partner violence (IPV), the definitions of common coping strategies and the two-dimensional model of coping styles (emotion-or problem-focused) may not fully delineate how these women manage their day-to-day lives. Using an Interpretive Description method and feminist standpoint principles, in-depth interviews were conducted with 40 Thai women regarding how they managed living in the context of IPV. Data were analyzed using an iterative thematic analysis procedure. In this study, the highly changeable and adaptive strategies use by participants could not be easily categorized into emotion-or action/problem-focused. Indeed, the strategies used by Thai women in this study were better described as survival focused. Based on our analysis, the process of managing their day-to-day life in the context of IPV revealed six major themes: keeping silent, disconnect between the fantasy of love and reality, seeking emotional support, ambivalence surrounding leaving, living with negative emotions, and despair and suicide. An undercurrent that was woven throughout multiple themes was the dominant lens of motherhood through which women made day-to-day decisions. These data also highlight the specific impacts that Thai society and religious beliefs have on increasing the risk of IPV and maintaining its duration. All levels of government, religious leaders, and public policy makers must engage in intersectoral initiatives to make public what is now private. Social and health service providers must create safe spaces where women can disclose IPV and where they can get funded multilevel supports to help them live independent of violence. The participants’ stories give voice to why Thai health professionals need to fully engage with women to understand the past and current contexts of women’s lives and how their experiences impact their health.